(untitled) (Malaysian Journal of Civil Engineering, 2018)
The expertise and the testing of structures with reinforced concrete that are existing or under construction often require the evaluation of the quality of concrete. The non-destructive test permitted to evaluate the state of their structures but also to assess the bearing capacity or to predict their durability. These techniques are generally influenced by several factors, generally humidity, for example, the speed of sound relied by varies humidity in concrete. The objective of this research is to study the durability of concrete the sanitation networks in the region of Ouargla - Algeria under the effect of sulphates agents. In this experimental, the specimen concrete conserved in different real environment, and these results were compared than those specimens curing with drinking water. Finally, they concluded the concrete specimens conserved in waste water have acceptable mechanical characteristics than those specimens curing in water, and it is obtained a regression of 3% the strength compressive to the age 365 days. But the exposure of concrete specimens to H2S gas, it is obtained a degradation accelerated in particular after 90 days to age, where a regression to 36% of the compressive strength than specimens curing in water at the age 365 days. The sanitation networks (pipes and manholes) of Ouargla – Algeria are a low durability under the effect of H2S gas sulphates. For increase the durability of pipes and manholes the Ouargla, it proposed the substitution by pipes and manholes in polyester materiel.